YouTuber Income from an Islamic Financial Perspective - Nulhakim, Naufal Allam; Hidayat, Rahmat (RAFAHIYA Jurnal Ekonomi dan Syariah, 2025)
This study aims to analyze the suitability of receiving income from YouTube with the principles of Islamic law. With the increase in the number of individuals working as content creators on the YouTube platform, a debate has arisen regarding the halal status of income earned from advertisements, sponsorships, and other forms of monetization from an Islamic perspective. This study evaluates the legal validity of income generated from YouTube and identifies the criteria that must be met for such income to be categorized as halal. The method used in this research is a literature study with a fiqh muamalah approach, which involves analyzing the type of content produced and the revenue generation mechanism based on the principles of Islamic law. The results reveal that revenue from YouTube can be categorized as halal if it does not involve elements that are contrary to Islamic teachings, such as pornography, gambling, and fraud, and is obtained through a fair mechanism that does not harm other parties. Thus, this study concludes that earning income from YouTube is permissible in Islam, as long as the uploaded content remains within the bounds of sharia norms and the source of income is obtained through ethical means and in accordance with the provisions of Islamic law.